Efficacy and safety of traditional Chinese medicine Elian Granule for chronic atrophic gastritis: a multi-center, randomized, double-blind, placebo-controlled study - Jia, Qingling; Jia, Yuebo; Chen, Yongqi; Guo, Likun; Wu, Chenheng; Cong, Jun; Gu, Zhijian; Li, Xuejun; Fang, Shengquan; Liu, Zhuhua; Jiang, Kailin; Liu, Xuejiao; et al. (Frontiers in Pharmacology, 2025)
ObjectiveThis multi-center, randomized, double-blind, placebo-controlled study aimed to evaluate the clinical efficacy and safety of Elian Granule in treating chronic atrophic gastritis (CAG).MethodsOver a 24-week period, 240 CAG patients were randomized to receive either Elian Granule or placebo. Primary outcomes included histological improvement of gastric mucosa via biopsy, while secondary outcomes assessed dyspepsia symptom scores and quality of life (QOL) scores. Safety was monitored through physical examinations, laboratory tests (blood and urine tests, liver function, and renal function), and electrocardiograms (ECGs).ResultsThe Elian Granule group exhibited significantly higher improvement rates in gastric mucosal atrophy (76.29% vs. 48.96%, P < 0.001) and intestinal metaplasia (62.89% vs. 34.38%, P < 0.001) compared to the placebo group. Total dyspepsia scores improved at 4, 12, and 24 weeks (P < 0.001), the individual symptom scores showed significant improvement in epigastric pain, epigastric distension, epigastric discomfort, early satiety, heartburn, belching and acid reflux at both the 4-week and 12-week timepoints (P < 0.05, P < 0.01, P < 0.001), of these, epigastric pain, epigastric distension, early satiety, belching and acid reflux maintained their statistically significant improvement through the 24-week evaluation period (P < 0.05, P < 0.01, P < 0.001). The total effective rate for symptom relief was 85.57% in the Elian group versus 47.92% in the placebo group (P < 0.001). QOL scores for physical health (GH, PF, BP, and PCS total score) and mental health (VT, SF, MH, and MCS total score) also improved significantly (P < 0.05, P < 0.01). No adverse impact was observed.ConclusionElian Granule significantly improves gastric mucosal atrophy and intestinalization, alleviates dyspeptic symptoms, and enhances QOL in CAG patients, demonstrating a favorable safety profile.Clinical Trial Registration:http://itmctr.ccebtcm.org.cn/zh-CN/Home/ProjectView?pid=7a00ecee-da6a-4939-bae1-e6a58cd97cdb, identifier ChiMCTR2000003929, 2020-9-13.